2021
DOI: 10.1002/ptr.7283
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and its role in modulating endoplasmic reticulum stress: A review

Abstract: The endoplasmic reticulum (ER) is the place where proteins and lipids are biosynthesized and where transmembrane proteins are folded. Both pathological and physiological situations may disturb the function of the ER, resulting in ER stress.Under stress conditions, the cells initiate a defensive procedure known as the unfolded protein response (UPR). Cases of severe stress lead to autophagy and/or the induction of cell apoptosis. Many studies implicate ER stress as a major factor contributing to many diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…Among all the flavonoids, glycosides of quercetin are known to have better absorption in the case of humans. It has a rapid metabolism and is excreted without accumulation in the body [45]. Quercetin is mostly absorbed in the small intestine.…”
Section: Onionmentioning
confidence: 99%
“…Among all the flavonoids, glycosides of quercetin are known to have better absorption in the case of humans. It has a rapid metabolism and is excreted without accumulation in the body [45]. Quercetin is mostly absorbed in the small intestine.…”
Section: Onionmentioning
confidence: 99%
“…It has a fast metabolic rate and a short half-life in blood, and its bioavailability is low [ 14 ]. Modern pharmacological studies have shown that QUR has anti-oxidation, anti-cancer, anti-allergy, anti-inflammation, anti-obesity and neuroprotection properties and shows an inhibition of platelet aggregation, enhancement of mitochondrial synthesis, regulation of intestinal microorganisms and other functions [ 8 , 9 , 15 ]. QUR can intervene in multiple pathological processes of PCOS through multi-target and multi-pathway and is expected to become a new treatment drug for PCOS.…”
Section: Introductionmentioning
confidence: 99%
“… 48 The unfolded protein response (UPR), also known as ER stress, is activated when the organism is stimulated by an excessive buildup of misfolded or unfolded proteins. 49 Under normal conditions, ER transmembrane proteins require IRE1, PERK, and ATF6 to form a stable complex with regulatory protein GRP78. After the abnormally excessive accumulation of ER proteins, these proteins dissociate from their corresponding regulatory proteins, thereby activating ER stress pathways, including the PERK/eIF2α/ATF4 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…48 The unfolded protein response (UPR), also known as ER stress, is activated when the organism is stimulated by an excessive buildup of misfolded or unfolded proteins. 49 Under normal conditions, ER transmembrane proteins require IRE1, PERK, and ATF6 to form…”
mentioning
confidence: 99%